Gender Differences in Neural Responses to Perceptually Invisible Fearful Face—An ERP Study - Lee, Seung A.; Kim, Chai-Youn; Shim, Miseon; Lee, Seung-Hwan (Frontiers in Behavioral Neuroscience, 2017)
Women tend to respond to emotional stimuli differently from men. This study aimed at investigating whether neural responses to perceptually “invisible” emotional stimuli differ between men and women by exploiting event-related potential (ERP). Forty healthy participants (21 women) were recruited for the main experiment. A control experiment was conducted by excluding nine (7 women) participants from the main experiment and replacing them with additional ten (6 women) participants (total 41 participants) where Beck’s Anxiety Inventory (BAI) and Beck’s Depression Inventory (BDI) scores were controlled. Using the visual backward masking paradigm, either a fearful or a neutral face stimulus was presented in varied durations (subthreshold, near-threshold or suprathreshold) followed by a mask. Participants performed a two-alternative forced choice (2-AFC) emotion discrimination task on each face. Behavioral analysis showed that participants were unaware of masked stimuli of which duration was the shortest and, therefore, processed at subthreshold. Nevertheless, women showed significantly larger response in P100 amplitude to subthreshold fearful faces than men. This result remained consistent in the control experiment. Our findings indicate gender-differences in neural response to subthreshold emotional face, which is reflected in the early processing stage.